Structural performance of optimised spirally deformed steel fibre. (15th September 2020) - Hajsadeghi, Mohammad; Chin, Chee Seong; Jones, Stephen W.
Highlights: The structural contribution of an optimised spirally deformed steel fibre is assessed. Two types of SFRC beams, shear-critical and flexure-critical, are tested experimentally. The results indicate the favourable contribution of the fibre to the ultimate capacity of the beams. A shear design equation for SFRC beams with the fibre is proposed. Abstract: The capability of steel fibres in stress transferring across the cracked sections (bridging effect) could be employed to enhance the concrete role (especially in tension zones) in the overall load bearing capacity of Reinforced Concrete (RC) members. However, the structural applications of Fibre Reinforced Concrete (FRC) is limited mainly due to the poor performance of existing fibres on the market (softening response). The continuous pullout load decay, i.e. softening response, cannot result in a major contribution of fibres to the ultimate load bearing capacity of RC members. In this paper, the structural contribution of an optimised spirally deformed steel fibre engineered by the authors possessing hardening response in normal concrete is examined experimentally. To this end, a structural testing programme consists of two sets of RC beams, i.e. shear-critical and flexure-critical, is designed such that the shear and flexural contribution of the spiral fibre can be assessed individually. Various experiment parameters are considered in the testing programme. The test results reveal that such a fibre could be employed as partial/full replacement for conventional reinforcement in RC beams. A shear design equation for RC beams incorporating the new fibre is also proposed.